Preparation method of lithium ion battery pre-lithiation diaphragm

By preparing a composite pre -lithium diaphragm in a lithium ion battery, the mixed slurry of orthopedic lithium, CNT, and polyiline is used for coating to solve the conductivity and stability of the existing lithium ion battery ion battery orthopedic lithium supplement agent The problem realizes higher energy density and cycle life.

CN119381691APending Publication Date: 2025-01-28JIANGXI GANFENG BATTERY TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411534467.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive lithium supplement agents have problems such as high alkali residue on the surface of the material, extremely poor conductivity, easy decomposition, easy powder loss of the electrode sheet, structural collapse and safety hazards.

Method used

Adopting a pre-lithium-based septum preparation method of lithium ion battery, adding n-di metamimamicamine solvents by mixing orthopedic lithium, CNT, and polyiline in a certain proportion, and using a extruder The material is evenly applied to the side of the PE diaphragm, and then dried in a vacuum oven.

Benefits of technology

Effectively improve the moisture of the electrolyte, provide higher lithium ion ratio capacity, reduce the impact of gas generation and Lifeo2 residues, reduce the battery's electrochemical impedance, enhance the metastatic dynamics of LI+, increase the battery's battery Energy density and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381691A_ABST
    Figure CN119381691A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery pre-lithiation diaphragm preparation method, which comprises: S1, uniformly mixing a positive electrode lithium supplementing agent, CNT and polyaniline by using a stirrer to obtain a slurry A, S2, adding an N-dimethylformamide solvent, mixing with the slurry A to obtain a slurry B, and S3, carrying out vacuum drying to obtain a lithium ion battery pre-lithiation diaphragm, uniformly coating one side of a PE diaphragm with the slurry B through a die head by using an extrusion type coating machine, and performing drying treatment in a vacuum drying oven; according to a conventional positive electrode lithium supplementing agent adding method, a positive electrode main material is directly added in the positive electrode homogenizing process, so that the energy density of a battery cell is reduced, the problems can be effectively solved through the prepared composite lithium supplementing diaphragm, the wettability of an electrolyte can be effectively improved, and higher lithium ion specific capacity can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and more specifically, to a method for preparing a pre-lithiation diaphragm for a lithium ion battery. Background Art

[0002] In recent years, lithium-ion batteries have developed rapidly and are widely used in consumer electronics, electric vehicles, energy storage, and various types of power tools. During the formation of lithium-ion batteries, lithium ions generate SEI films on the surface of the negative electrode, consuming active lithium, resulting in battery capacity loss. By introducing lithium ions in advance, active lithium can be compensated to achieve the effect of improving the energy density of lithium-ion batteries. Pre-lithiation can improve the shortcoming of low initial efficiency, give full play to its high capacity advantages, further improve battery cycle performance and energy density, and greatly promote the development of lithium-ion batteries.

[0003] In the development of lithium-ion batteries, many positive electrode lithium supplements are regarded as ideal pre-lithiation materials because they all have high theoretical capacity (400 mAh / g - 800 mAh / g) and suitable capacity-playing voltage platform for positive electrode lithium supplements. In addition, Li5FeO4 has an inverse fluorite structure, which is conducive to the deintercalation of lithium ions and helps to improve the charge and discharge performance of the battery.

[0004] The existing various types of positive electrode lithium supplements also have some difficult-to-solve problems, mainly including high residual alkali on the material surface, extremely poor conductivity of the material itself, easy decomposition during the coating process, easy powder loss of the electrode, and easy structural collapse. In addition, oxygen may be generated during the charging and discharging process, causing battery inflation and posing safety hazards, affecting the long-term cycle stability of the battery.

[0005] In view of the above-mentioned problems existing in the prior art, the present invention proposes a novel method for preparing a pre-lithiation separator for lithium-ion batteries, which solves the problems of difficulty in slurry coating, decreased conductivity, easy powder loss of pole pieces, structural collapse and aggravated side reactions of the electrolyte caused by high residual alkali on the surface of the positive electrode lithium supplement. Summary of the invention

[0006] The purpose and effect of the present invention are achieved by the following specific technical means: A method for preparing a pre-lithiation separator for a lithium-ion battery comprises the following steps: S1, the positive electrode lithium supplement, CNT and polyaniline are mixed evenly with a stirrer to obtain slurry A S2, then adding N-dimethylformamide solvent and mixing with slurry A to obtain slurry B; S3, using an extrusion coater to evenly apply slurry B on one side of the PE diaphragm through a die head, and drying it in a vacuum oven.

[0007] Preferably, in step S1, the type of the positive electrode lithium supplement is a combination of one or more of lithium nickelate, lithium ferrite, lithium squarate, lithium orthosilicate, and lithium fluoride.

[0008] Preferably, in step S1, the type of polyaniline is a combination of one or more of ground state polyaniline, granular polyaniline, fibrous polyaniline, composite polyaniline and nanotube polyaniline.

[0009] Preferably, in step S1, the CNT is a combination of one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, double-walled carbon nanotubes, doped carbon nanotubes, carbon nanotube foams, and carbon nanotube films.

[0010] Preferably, in step S1, the ratio of the positive electrode lithium supplement agent: CNT: polyaniline is one of 80:10:10, 70:15:15, 60:20:20, 50:30:20 and 50:20:30.

[0011] Preferably, in step S1, the stirrer speed is set to 1200 r / min-1800 r / min, and the mixing time is 50-600 min.

[0012] Preferably, in step S2, the solid content of slurry B is between 50% and 70%.

[0013] Preferably, in step S3, the extrusion rate of the extrusion coater is 200-1000 mL / min, and the coating speed is 0.1-10 m / min.

[0014] Preferably, in step S3, the vacuum oven drying process has a vacuum degree of 0 to -0.5 MPa and a drying temperature of 90-120°C.

[0015] Beneficial effects of the present invention: 1. The conventional method of adding positive electrode lithium supplement is to directly add the positive electrode main material during the positive electrode homogenization process, which will lead to a decrease in the energy density of the battery cell. The composite lithium supplement diaphragm prepared by the present invention can effectively solve these problems. The present invention can effectively improve the wettability of the electrolyte and provide a higher lithium ion specific capacity.

[0016] 2. By reducing the effects of gas generation and LiFeO2 residues, the electrochemical impedance of the battery is reduced and the transfer kinetics of interfacial lithium ions are accelerated. The separator changes the composition of SEI by providing oxygen atoms to form Li2O, thereby enhancing the transfer kinetics of Li+.

[0017] 3. By adding positive electrode lithium supplement to the separator, the lithium loss of LFP battery in the first cycle can be compensated, and the energy density and cycle life of the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The present invention will be further described below in conjunction with the accompanying drawings.

[0019] Figure 1 Schematic diagram of the lithium-supplementing diaphragm prepared in the present invention. DETAILED DESCRIPTION

[0020] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail in the specific embodiments. The following embodiments are only examples of implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the scope of the present invention are all within the scope of patent protection of the present invention.

[0021] A method for preparing an organic pre-lithiation diaphragm material comprises the following steps: The positive electrode lithium supplement agent, CNT and polyaniline are mixed evenly in a certain proportion, and then N, N-dimethylformamide (DMF) solvent is added to mix; The type of positive electrode lithium supplement is one or more mixtures of lithium nickelate, lithium ferrite, lithium squarate, lithium orthosilicate, and lithium fluoride. In the experimental preparation process of this patent, comprehensive multi-angle performance analysis and actual production conditions are combined. The preferred lithium supplement is lithium ferrite (Li5FeO4). In order to improve conductivity, enhance mechanical strength, improve electrolyte wettability, promote uniform dispersion of LFO, and prevent subsequent cycles from falling off, ground state polyaniline is more preferred; CNT is single-walled carbon nanotube, multi-walled carbon nanotube, double-walled carbon nanotube, doped carbon nanotube, carbon nanotube foam, carbon nanotube film, or one or more mixtures thereof. Considering the catalytic effect on Li5FeO4, the conductive effect, the dispersion performance and the mechanical strength, single-walled carbon nanotube (SWCNTs) is more preferred. The ratio of positive electrode lithium supplement: CNT: polyaniline is 80:10:10 or 70:15:15 or 60:20:20 or 50:30:20 or 50:20:30. The stirrer speed is set to 1200 r / min -1800 r / min, and the mixing time is 50-600min. The slurry preparation process is a high-speed centrifugal defoamer 300-500rpm premixing time of 5-15min, and a secondary mixing 1500-2500rpm mixing time of 30-180min; The solid content of the mixed slurry is between 50% and 70%. The preferred solid content is 55% considering the comprehensive slurry dispersion uniformity and coating efficiency. Then, an extrusion coater is used to evenly apply the slurry to one side of the PE diaphragm through a die head, and then dried in a vacuum oven. The extrusion rate of the extrusion coater is 200-1000mL / min, the coating speed is 0.1-10m / min, and the vacuum oven drying process has a vacuum degree of 0 to -0.5Mpa and a drying temperature of 90-120°C.

[0022] Set the extrusion rate of the extrusion coater to 250mL / min, the coating speed to 2m / min, the vacuum oven drying process to a vacuum degree of -0.1Mpa, a drying temperature of 90°C, the thickness of the PE separator to 3-50μm, the porosity to 10-70%, the thickness of the lithium replenishment layer to 0.1μm-3μm, and the thickness of the PE separator to 9μm, the porosity to 40%, and the thickness of the lithium replenishment layer to 0.5μm. Example 1

[0023] S1: The positive electrode uses lithium iron phosphate, the negative electrode uses graphite, the electrolyte uses carbonate electrolyte, and the diaphragm uses conventional PE diaphragm (9μm, porosity 40%). No special treatment is done on it. The aluminum tabs and copper-plated nickel tabs are led out. A 3.5Ah wound soft-pack battery is prepared according to industry standards. After liquid injection, it is packaged with aluminum-plastic film. The battery cell is hot-pressed at a pressure of 20MPa, a temperature of 90℃, and a time of 120s to obtain a 3.5Ah soft-pack battery, recorded as battery cell A. The prepared battery cell is charged to 4.25V and the electrical performance is tested. Example 2

[0024] S1: The positive electrode uses lithium iron phosphate (1% LFP is replaced by Li5FeO4), the negative electrode uses graphite, the electrolyte uses carbonate electrolyte, and the diaphragm uses a conventional PE diaphragm (9μm, porosity 40%), without any special treatment, and the aluminum tabs and copper-plated nickel tabs are drawn out. A 3.5Ah wound soft-pack battery is prepared according to industry standards, and after injection, it is encapsulated with aluminum-plastic film. The battery cell is hot-pressed at a pressure of 20MPa, a temperature of 90℃, and a time of 120s to obtain a 3.5Ah soft-pack battery, recorded as battery cell B. The prepared battery cell is charged to 4.25V and the electrical performance is tested. Example 3

[0025] S1: Li5FeO4: CNT: polyaniline were mixed in a ratio of 80:10:10, and the stirrer speed was set to 1500 r / min. Then, N,N-dimethylformamide (DMF) was added according to 55% solid content to prepare the slurry. A high-speed centrifugal defoamer was used at 450 rpm, premixed for 15 minutes, and then mixed at 2300 rpm for 90 minutes to obtain the slurry to be coated.

[0026] S2: Then use an extrusion coater to control the extrusion rate to 250 mL / min and the coating speed to 2 m / min.

[0027] The slurry was evenly applied to one side of a PE diaphragm (9 μm, porosity 40%) through a die head to prepare a lithium replenishing layer with a thickness of 0.5 μm. The slurry was then placed in a vacuum oven with a vacuum degree set to -0.1 MPa and a drying temperature set to 90°C for drying. A lithium replenishing diaphragm material was obtained.

[0028] S3: Preparation of battery cells, using lithium iron phosphate for the positive electrode, graphite for the negative electrode, carbonate electrolyte for the electrolyte, and the lithium-supplemented diaphragm prepared in S1 above as the diaphragm, with aluminum tabs and copper-plated nickel tabs drawn out. Prepare 3.5Ah wound soft-pack batteries according to industry standards, encapsulate with aluminum-plastic film after injection, and hot-press the battery cells at a pressure of 20MPa, a temperature of 90°C, and a time of 120s to obtain 3.5Ah soft-pack batteries, recorded as battery cells C, charge the prepared battery cells to 4.25V, and conduct electrical performance tests. Example 4

[0029] S1: Li5FeO4: CNT: polyaniline were mixed in a ratio of 70:15:15, the stirrer speed was set to 1500 r / min, and then N, N-dimethylformamide (DMF) was added at a solid content of 55% to prepare the slurry. A high-speed centrifugal defoamer was used at 450 rpm, premixed for 15 minutes, and then mixed at 2300 rpm for 90 minutes to obtain the slurry to be coated.

[0030] S2: Then use an extrusion coater to control the extrusion rate to 250 mL / min and the coating speed to 2 m / min.

[0031] The slurry was evenly applied to one side of a PE diaphragm (9 μm, porosity 40%) through a die head to prepare a lithium replenishing layer with a thickness of 0.5 μm. The slurry was then placed in a vacuum oven with a vacuum degree of -0.1 MPa and a drying temperature of 90°C for drying. A Li5FeO4 lithium replenishing diaphragm material was obtained.

[0032] S3: Preparation of battery cells, using lithium iron phosphate for the positive electrode, graphite for the negative electrode, carbonate electrolyte for the electrolyte, and the lithium-supplemented diaphragm prepared in S1 above as the diaphragm, with aluminum tabs and copper-plated nickel tabs drawn out. Prepare 3.5Ah wound soft-pack batteries according to industry standards, encapsulate with aluminum-plastic film after injection, and hot-press the battery cells at a pressure of 20MPa, a temperature of 90°C, and a time of 120s to obtain 3.5Ah soft-pack batteries, recorded as battery cells D, and charge the prepared battery cells to 4.25V, and conduct electrical performance tests. Example 5

[0033] S1: Li5FeO4: CNT: polyaniline were mixed in a ratio of 60:20:20, and the stirrer speed was set to 1500 r / min. Then, N,N-dimethylformamide (DMF) was added at a solid content of 55% to prepare the slurry. A high-speed centrifugal defoamer was used at 450 rpm, premixed for 15 minutes, and then mixed at 2300 rpm for 90 minutes to obtain the slurry to be coated.

[0034] S2: Then use an extrusion coater to control the extrusion rate to 250 mL / min and the coating speed to 2 m / min.

[0035] The slurry was evenly applied to one side of a PE diaphragm (9 μm, porosity 40%) through a die head to prepare a lithium replenishing layer with a thickness of 0.5 μm. The slurry was then placed in a vacuum oven with a vacuum degree of -0.1 MPa and a drying temperature of 90°C for drying. A Li5FeO4 lithium replenishing diaphragm material was obtained.

[0036] S3: Preparation of battery cells, using lithium iron phosphate for the positive electrode, graphite for the negative electrode, carbonate electrolyte for the electrolyte, and the lithium-supplemented diaphragm prepared in S1 above as the diaphragm, with aluminum tabs and copper-plated nickel tabs drawn out. Prepare 3.5Ah wound soft-pack batteries according to industry standards, encapsulate with aluminum-plastic film after injection, and hot-press the battery cells at a pressure of 20MPa, a temperature of 90°C, and a time of 120s to obtain 3.5Ah soft-pack batteries, recorded as battery cells E, and charge the prepared battery cells to 4.25V, and conduct electrical performance tests. Example 6

[0037] S1: Li5FeO4: CNT: polyaniline were mixed in a ratio of 50:30:20, and the stirrer speed was set to 1500 r / min. Then, N,N-dimethylformamide (DMF) was added according to 55% solid content to prepare the slurry. A high-speed centrifugal defoamer was used at 450 rpm, premixed for 15 minutes, and then mixed at 2300 rpm for 90 minutes to obtain the slurry to be coated.

[0038] S2: Then use an extrusion coater to control the extrusion rate to 250 mL / min and the coating speed to 2 m / min.

[0039] The slurry was evenly applied to one side of a PE diaphragm (9 μm, porosity 40%) through a die head to prepare a lithium replenishing layer with a thickness of 0.5 μm. The slurry was then placed in a vacuum oven with a vacuum degree of -0.1 MPa and a drying temperature of 90°C for drying. A Li5FeO4 lithium replenishing diaphragm material was obtained.

[0040] S3: Preparation of battery cells, using lithium iron phosphate for the positive electrode, graphite for the negative electrode, carbonate electrolyte for the electrolyte, and the lithium-supplemented diaphragm prepared in S1 above as the diaphragm, with aluminum tabs and copper-plated nickel tabs drawn out. Prepare 3.5Ah wound soft-pack batteries according to industry standards, encapsulate with aluminum-plastic film after injection, and hot-press the battery cells at a pressure of 20MPa, a temperature of 90°C, and a time of 120s to obtain 3.5Ah soft-pack batteries, recorded as battery cells F, and charge the prepared battery cells to 4.25V, and conduct electrical performance tests. Example 7

[0041] S1: Li5FeO4: CNT: polyaniline were mixed in a ratio of 50:20:30, the stirrer speed was set to 1500 r / min, and then N, N-dimethylformamide (DMF) was added at a solid content of 55% to prepare the slurry. A high-speed centrifugal defoamer was used at 450 rpm, premixed for 15 minutes, and then mixed at 2300 rpm for 90 minutes to obtain the slurry to be coated.

[0042] S2: Then use an extrusion coater to control the extrusion rate to 250 mL / min and the coating speed to 2 m / min.

[0043] The slurry was evenly applied to one side of a PE diaphragm (9 μm, porosity 40%) through a die head to prepare a lithium replenishing layer with a thickness of 0.5 μm. The slurry was then placed in a vacuum oven with a vacuum degree of -0.1 MPa and a drying temperature of 90°C for drying. A Li5FeO4 lithium replenishing diaphragm material was obtained.

[0044] S3: Preparation of battery cells, using lithium iron phosphate for the positive electrode, graphite for the negative electrode, carbonate electrolyte for the electrolyte, and the lithium-supplemented diaphragm prepared in S1 above as the diaphragm, with aluminum tabs and copper-plated nickel tabs drawn out. Prepare 3.5Ah wound soft-pack batteries according to industry standards, encapsulate with aluminum-plastic film after injection, and hot-press the battery cells at a pressure of 20MPa, a temperature of 90°C, and a time of 120s to obtain 3.5Ah soft-pack batteries, recorded as battery cells G, and charge the prepared battery cells to 4.25V, and conduct electrical performance tests.

[0045] Example Cell formation to 4.25V Capacity mAh Internal resistance Cycle performance (cutoff 80%) Energy density Wh / kg.

[0046] Example The battery is charged to 4.25V capacity mAh Internal resistance Cyclic performance (cut-off 80%) Energy densityWh / kg 1 3915.73 7.3mΩ 3000 times 157.31 2 4123.65 6.3mΩ 7300 times 162.42 3 4378.89 4.3mΩ 9000 times 164.24 4 4321.25 5.6mΩ 8500 times 163.78 5 4289.97 6.0mΩ 7800 times 162.54 6 4230.54 6.3mΩ 6500 times 162.15 7 4254.63 6.1mΩ 6700 times 162.57 By comparing the above examples 1, 2, 3, 4, 5, 6, and 7, it can be seen that different amounts of Li5FeO4 added have a significant effect on the battery cell prepared by the method of the present invention. When the ratio of Li5FeO4:CNT:polyaniline is 80:10:10, the Li5FeO4 lithium supplement has a better catalytic effect and can catalyze a higher capacity during formation. An organic pre-lithiation diaphragm material is successfully prepared by the present invention. The composite diaphragm can effectively improve the energy density of the battery cell, reduce the internal resistance of the battery cell, and improve the cycle performance of the battery cell.

Claims

1. A method for preparing a pre-lithiation separator for a lithium-ion battery, characterized in that: The following steps are involved: S1, the positive electrode lithium supplement, CNT and polyaniline are mixed evenly with a stirrer to obtain slurry A S2, then adding N-dimethylformamide solvent and mixing with slurry A to obtain slurry B; S3, using an extrusion coater to evenly apply slurry B on one side of the PE diaphragm through a die head, and drying it in a vacuum oven.

2. The method for preparing a lithium ion battery pre-lithiation diaphragm according to claim 1, characterized in that: In the step S1, the type of the positive electrode lithium supplement is a combination of one or more of lithium nickelate, lithium ferrite, lithium squarate, lithium orthosilicate, and lithium fluoride.

3. The method for preparing a lithium ion battery pre-lithiation diaphragm according to claim 1, characterized in that: In the step S1, the type of polyaniline is a combination of one or more of ground state polyaniline, granular polyaniline, fibrous polyaniline, composite polyaniline, and nanotube polyaniline.

4. The method for preparing a lithium ion battery pre-lithiation diaphragm according to claim 1, characterized in that: In the step S1, the CNT is a single-walled carbon nanotube, a multi-walled carbon nanotube, a double-walled carbon nanotube, a doped carbon nanotube, a carbon nanotube foam, a carbon nanotube film, or a combination of one or more thereof.

5. The method for preparing a pre-lithiation separator for a lithium-ion battery according to claim 1, characterized in that: In the step S1, the ratio of the positive electrode lithium supplement agent: CNT: polyaniline is one of 80:10:10, 70:15:15, 60:20:20, 50:30:20 and 50:20:

30.

6. The method for preparing a lithium ion battery pre-lithiation diaphragm according to claim 1, characterized in that: In step S1, the stirrer speed is set to 1200 r / min-1800 r / min, and the mixing time is 50-600 min.

7. The method for preparing a pre-lithiation separator for a lithium-ion battery according to claim 1, characterized in that: In step S2, the solid content of slurry B is between 50% and 70%.

8. The method for preparing a lithium-ion battery pre-lithiation separator according to claim 1, characterized in that: In the step S3, the extrusion rate of the extrusion coater is 200-1000 mL / min, and the coating speed is 0.1-10 m / min.

9. The method for preparing a pre-lithiation separator for a lithium-ion battery according to claim 1, characterized in that: In step S3, the vacuum oven drying process has a vacuum degree of 0 to -0.5 MPa and a drying temperature of 90-120°C.